Catch up growth and pancreatic function in growth retarded neonates. Issue 3 (November 1995) - Williams, S. P.; Durbin, G. M.; Morgan, M. E.; Booth, I. W.
Abstract : To test the hypothesis that relative pancreatic dysfunction is a determinant of catch up growth in small for gestational age (SGA) babies, 47 such babies (median gestation 38 weeks; range 27-41) and 41 appropriate for gestational age (AGA) babies matched for sex, race, and gestational age were recruited. Anthropometry was performed within 48 hours of birth and at 6 months. Faecal chymotrypsin activities were measured at 0-2 days, 14 days, 6 weeks and 6 months. At 6 months 30 SGA infants and 25 AGA infants were remeasured. In each group, median stool chymotrypsin activities doubled between 0-2 days and 6 months (9.0-25.5 IU/g SGA group; 11.6-25.3 IU/g AGA group). SGA babies had significantly lower chymotrypsin activities at 14 days (10.9 U/g) than AGA babies (15.5 U/g). In the SGA group faecal chymotrypsin activities at 0-2 days were strongly correlated with both catch up weight and with catch up length when corrected for the effects of birthweight. These data show that impaired pancreatic exocrine function at birth is associated with severe intrauterine malnutrition and with impaired catch up growth during the first 6 months of life.